2009
DOI: 10.1152/ajpgi.90318.2008
|View full text |Cite
|
Sign up to set email alerts
|

Every slow-wave impulse is associated with motor activity of the human stomach

Abstract: Using a newly developed high-resolution three-dimensional magnetic detector system (3D-MAGMA), we observed periodical movements of a small magnetic marker in the human stomach at the typical gastric slow-wave frequency, that is 3 min(-1). Thus we hypothesized that each gastric slow wave induces a motor response that is not strong enough to be detected by conventional methods. Electrogastrographies (EGG, Medtronic, Minneapolis, MN) for measurement of gastric slow waves and 3D-MAGMA (Innovent, Jena, Germany) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 46 publications
3
34
0
Order By: Relevance
“…This process can easily be detected by analyzing the frequencies of the marker movement. These frequencies are dominated by slow waves of 3 cycles per minute in the stomach [9] while 12 cycles per minute will dominate in the duodenum. Afterwards the tracked path is used to determine the place of dissolution in the small intestine or the colon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process can easily be detected by analyzing the frequencies of the marker movement. These frequencies are dominated by slow waves of 3 cycles per minute in the stomach [9] while 12 cycles per minute will dominate in the duodenum. Afterwards the tracked path is used to determine the place of dissolution in the small intestine or the colon.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements of the magnetic field produced by the magnetic marker in the phantom were performed using the high-resolution three-dimensional magnetic detection system 3D-MAGMA (Matesy GmbH, Jena, Thuringia, Germany) [9]. This device consists of 27 anisotropic magnetoresistive sensors which are arranged in nine sensor triplets (separated on three sensor board modules) enabling the detection of the magnetic field in three dimensions at room temperature.…”
Section: Sensor Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a scenario, the EPM could be mounted as end-effector on a robotic arm, as in [15], and real-time localization of the capsule (based on magnetic fields [36]) would allow the system to autonomously run the legged mechanism whenever the capsule does not follow the EPM movement. Additionally, contact or pressure sensors on the surface of the capsule could be exploited in order to autonomously trigger activation of the legs.…”
Section: Discussionmentioning
confidence: 99%
“…Most mechanical and electrical properties in human GI tract have been investigated using electrogastrograph (EGG) and ultrasonography (Hocke et al, 2009;Matsumoto et al, 2009), although several in vitro GI motility studies have been reported (Tonini et al, 2000;Farrelly et al, 2003;Severi et al, 2006;Wang et al, 2007). In this in vitro study, we first characterized mechanical properties.…”
Section: Discussionmentioning
confidence: 99%